2023
DOI: 10.3390/ijerph20054472
|View full text |Cite
|
Sign up to set email alerts
|

Adventure Recreation in Blue Spaces and the Wellbeing of Young Polish Adults

Abstract: The aim of this study was to assess the wellbeing of 248 young Polish adults between 18 and 26 years old (M = 22.35; SD = 2.20) involved in adventure blue space recreational activities. The adventure water recreational activities were measured by using a questionnaire specially designed for the purpose of this study. This questionnaire consisted of two subscales: adventure recreation associated with water risks and adventure recreation associated with weather risks. In turn, wellbeing was measured using six sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 88 publications
(98 reference statements)
0
0
0
Order By: Relevance
“…A greater focus on inland blue space research is warranted to better understand the complex relationship between inland blue space exposure and health and wellbeing outcomes. Initial research has identified differences in the wellbeing outcomes associated with recreational activities at different blue space types, with coastal recreation often leading to higher wellbeing outcomes for visitors than activities at inland blue spaces [19][20][21]. Differences have also been identified in user groups between blue space types, with inland blue spaces shown to attract visits from individuals with higher socio-economic statuses compared to coastal areas [22].…”
Section: Introductionmentioning
confidence: 99%
“…A greater focus on inland blue space research is warranted to better understand the complex relationship between inland blue space exposure and health and wellbeing outcomes. Initial research has identified differences in the wellbeing outcomes associated with recreational activities at different blue space types, with coastal recreation often leading to higher wellbeing outcomes for visitors than activities at inland blue spaces [19][20][21]. Differences have also been identified in user groups between blue space types, with inland blue spaces shown to attract visits from individuals with higher socio-economic statuses compared to coastal areas [22].…”
Section: Introductionmentioning
confidence: 99%